![1)7*(\frac{1}{7})^{2+\frac{1}{2}log_{\frac{1}{7}}49} =7*7^{-2+log_{7}\sqrt{49}}=7^{1-2+log_{7}7}=7^{-1+1}=7^{0}=1 1)7*(\frac{1}{7})^{2+\frac{1}{2}log_{\frac{1}{7}}49} =7*7^{-2+log_{7}\sqrt{49}}=7^{1-2+log_{7}7}=7^{-1+1}=7^{0}=1](https://tex.z-dn.net/?f=1%297%2A%28%5Cfrac%7B1%7D%7B7%7D%29%5E%7B2%2B%5Cfrac%7B1%7D%7B2%7Dlog_%7B%5Cfrac%7B1%7D%7B7%7D%7D49%7D+%3D7%2A7%5E%7B-2%2Blog_%7B7%7D%5Csqrt%7B49%7D%7D%3D7%5E%7B1-2%2Blog_%7B7%7D7%7D%3D7%5E%7B-1%2B1%7D%3D7%5E%7B0%7D%3D1)
[tex]=10^{lg\sqrt{\frac{125}{5} } }=10^{lg\sqrt{25}}=10^{lg5}=5" alt="10^{\frac{1}{2}lg125-2lg\sqrt[4]{5}}=10^{lg\sqrt{125}-lg(5^{\frac{1}{4})^{2} } }=10^{lg\sqrt{125}-lg\sqrt{25}}=
[tex]=10^{lg\sqrt{\frac{125}{5} } }=10^{lg\sqrt{25}}=10^{lg5}=5" align="absmiddle" class="latex-formula">
![-log_{2}(log_{2}\sqrt{\sqrt[8]{2}})=-log_{2}(log_{2}((2^{\frac{1}{8}})^{\frac{1}{2}}=-log_{2}(log_{2}2^{\frac{1}{16}})= -log_{2}(log_{2}\sqrt{\sqrt[8]{2}})=-log_{2}(log_{2}((2^{\frac{1}{8}})^{\frac{1}{2}}=-log_{2}(log_{2}2^{\frac{1}{16}})=](https://tex.z-dn.net/?f=-log_%7B2%7D%28log_%7B2%7D%5Csqrt%7B%5Csqrt%5B8%5D%7B2%7D%7D%29%3D-log_%7B2%7D%28log_%7B2%7D%28%282%5E%7B%5Cfrac%7B1%7D%7B8%7D%7D%29%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%3D-log_%7B2%7D%28log_%7B2%7D2%5E%7B%5Cfrac%7B1%7D%7B16%7D%7D%29%3D+)
![=-log_{2}\frac{1}{16}=-log_{2}2^{-4}=-(-4)=4 =-log_{2}\frac{1}{16}=-log_{2}2^{-4}=-(-4)=4](https://tex.z-dn.net/?f=%3D-log_%7B2%7D%5Cfrac%7B1%7D%7B16%7D%3D-log_%7B2%7D2%5E%7B-4%7D%3D-%28-4%29%3D4)